2005
DOI: 10.1016/j.biocontrol.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of known and potential risks associated with exotic toadflax-feeding insects

Abstract: Hansen, Richard W.; and Markin, George P., "A retrospective analysis of known and potential risks associated with exotic toadflax-feeding insects" (2005 AbstractTo date, eight exotic toadXax-feeding insect species have been accidentally or intentionally introduced to North America. Reports on their establishment and impact have been recorded for more than 60 years. Environmental risks linked to biological control of toadXax were identiWed in terms of host resources and undesirable impacts on the target specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 93 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…Their presence is due both to unintentional and intentional introductions from Europe, along with their hosts L. vulgaris or the congeneric weedy species, Linaria dalmatica (L.) Miller and L. genistifolia (L.) Mill. Three adventitiously introduced seed-feeding beetles, Brachypterolus pulicarius (Linnaeus, 1758) (Coleoptera: Nitidulidae), Rhinusa antirrhini (Paykull, 1800) (formerly Gymnetron antirrhini), and Rhinusa neta (Germar, 1821) (formerly Gymnetron netum) (Coleoptera: Curculionidae), are now ubiquitous on North American L. vulgaris, either self-dispersed or intentionally spread as part of the North American toadflax biological control program (De Clerck-Floate and McClay 2013;De Clerck-Floate and Turner 2013;Sing et al 2005;Wilson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their presence is due both to unintentional and intentional introductions from Europe, along with their hosts L. vulgaris or the congeneric weedy species, Linaria dalmatica (L.) Miller and L. genistifolia (L.) Mill. Three adventitiously introduced seed-feeding beetles, Brachypterolus pulicarius (Linnaeus, 1758) (Coleoptera: Nitidulidae), Rhinusa antirrhini (Paykull, 1800) (formerly Gymnetron antirrhini), and Rhinusa neta (Germar, 1821) (formerly Gymnetron netum) (Coleoptera: Curculionidae), are now ubiquitous on North American L. vulgaris, either self-dispersed or intentionally spread as part of the North American toadflax biological control program (De Clerck-Floate and McClay 2013;De Clerck-Floate and Turner 2013;Sing et al 2005;Wilson et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of the mentioned insect species against invasive toadflaxes beginning in the 1960s (McClay and De Clerck-Floate 2002;Sing et al 2005;Wilson et al 2005;De Clerck-Floate and McClay 2013;De Clerck-Floate and Turner 2013), the reported efficacy of the majority of these on L. vulgaris has been minimal, with only M. janthinus recently showing some promise since its first releases in the 1990s in both the USA and Canada De Clerck-Floate and McClay 2013). Since 2000, several other European insects have been investigated for potential use against L. vulgaris, and the first of these, the shoot-galling weevil, Rhinusa pilosa (Gyllenhal) (Coleoptera: Curculionidae), was petitioned for release in the USA andCanada in 2012 (De ClerckFloate andMcClay 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The larvae develop inside the ovaries, stems, or roots of the host plants and are sometimes able to induce the formation of galls (Hoffmann 1958;Caldara 2001;Toševski et al 2011). Several species of the genus have been the subject of detailed ecological studies (De Clerck-Floate and Harris 2002;De Clerck-Floate and Miller 2002;McClay and De Clerck-Floate 2002;Sing et al 2005;Toševski et al 2011) as potential biological control agents for some species of toadflax (Linaria spp.) that were introduced into North America and have since become invasive (Vujnovic and Wein 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This aspect has not been investigated previously. It has been increasingly accepted within the field of biological control that microbial interactions are a considerable, significant factor in the biological control of invasive plants (Bacher et al, 2002;Lym and Carlson, 2002;Sing et al, 2005;Butler et al, 2006). This complements a large body of literature showing that exotic plant invasion is both affected by and affects the soil microbial ecology (Belnap and Phillips, 2001;Ehrenfeld et al, 2001;Ehrenfeld, 2003;Kourtev et al, 2002Kourtev et al, , 2003, including effects on plant succession (Van der Putten et al, 1993;Bever et al, 1997).…”
Section: Introductionmentioning
confidence: 99%